A Comparative Study on Regular Students’ Sensitivity at the Inclusive Education of Junior High School and Senior High School in Surakarta - Arozi Setiawan; Abdul Salim; Sunardi Sunardi (Journal of ICSAR, 2018)
Sensitivity is an ability to understanding an individual which is implemented into knowledge, attitude, and behavior. This study is aimed to know the level of regular students’ sensitivity at the inclusive education in the level education of Junior High School and Senior High School. The subjects of this research are the students of Junior High School and Senior High School, each of them is 45 students. The technique of collecting the data uses questionnaire. The technique of analyzing the data uses the normality test, homogeneity test, and independent t-test. The result of this research shows that the distribution of the data is normal, homogeny and the average of sensitivity value’s regular students at the level of Junior High Schoo is 127.98, while the average of sensitivity value’s regular students at the level of Senior High School is 133.89. Based on the result, it can be concluded that regular students’ sensitivity toward the children with special needs at the Senior High School is higher than Junior High School.